Portocaval venograft with an ameroid constrictor for treatment of intrahepatic portosystemic shunting in two dogs - Fraser, A.R.; Hosgood, G.L.; Richardson, J.L. (Australian Small Animal Veterinary Association, 2015)
CASE REPORT: A 2-year-old entire female Golden Retriever and 1-year-old entire male Newfoundland mixed-breed dog were diagnosed with a right division and a central division intrahepatic portosystemic shunt, respectively. The anomalous vessel was ligated in the first dog and attenuated with a cellophane band in the second. Portal hypertension was controlled in both dogs by creating a portocaval venograft, with an ameroid constrictor placed around the venografts to cause gradual attenuation. Both dogs improved clinically following surgery. Postoperative abdominal ultrasonography confirmed intrahepatic portosystemic shunt ligation and gradual attenuation of the portocaval venograft in the first dog but a thrombus was identified within the caudal vena cava 4 weeks after surgery. Postoperative abdominal ultrasonography 6 days after surgery of the second dog demonstrated a thrombus in the central branch of the portal vein; serial ultrasound showed progressive attenuation of the intrahepatic portosystemic shunt and venograft. Treatment of the thrombi included administration of clopidogrel, aspirin and dalteparin. The thrombus was <50% of its first documented size 15 weeks postoperatively in the first dog and was absent 5 weeks after surgery in the second dog. CONCLUSIONS: Controlling portal hypertension using a portocaval venograft with simultaneous occlusion or attenuation of an intrahepatic shunt showed encouraging results.